Analysis of Eustachian Tube Dysfunction by Dynamic Slow Motion Video Endoscopy and Eustachian Tube Dysfunction Questionnaire in Chronic Otitis Media - Han, Won Gue (Clin Exp Otorhinolaryngol, 2017)
OBJECTIVES: Eustachian tube dysfunction has been associated with most cases of middle-ear disease. We aimed to assess the effectiveness of dynamic slow motion video endoscopy (DSVE) as a test of eustachian tube dysfunction. Furthermore, we assessed the correlation of the test with the Valsalva maneuver, the seven-item Eustachian Tube Dysfunction Questionnaire (ETDQ-7), and intraoperative findings of the eustachian tube. METHODS: We retrospectively reviewed medical records from April to September 2014 to identify patients who were diagnosed with chronic otitis media (COM) at Korea University Ansan Hospital. They all underwent surgery because of COM without cholesteatoma and were assessed via the DSVE and ETDQ-7 to determine eustachian tube function. RESULTS: We reviewed 46 COM patients and examined 46 ears with COM and 46 ears on the contralateral side to COM that were thought to be normal. The mean DSVE grade in COM ears was 1.57±0.96, while the mean DSVE grade in contralateral ears was 1.15±0.94. The difference in DSVE between COM ears and normal ears was statistically significant (P=0.006). In the ETDQ-7, a higher score was related to intraoperative obstruction of the eustachian tube (P=0.012). CONCLUSION: DSVE and ETDQ-7 can provide information regarding preoperative status of eustachian tube dysfunction by measuring dynamic structural changes of the eustachian tube in combination with other diagnostic tests.